12 + (4x – 12) – 2x = (5 – 3x) + 10

Lamah Lamah    1   17.12.2021 12:37    0

Ответы
1836294 1836294  17.12.2021 12:40

12 + (4x – 12) – 2x = (5 – 3x) + 10;

12 + 4x – 12 – 2x = 5 – 3x + 10;

12 - 12 + 4x - 2x = 15 - 3x;

2x +3x = 15;

5x = 15;

x = 15 : 5;

x = 3.

ПОКАЗАТЬ ОТВЕТЫ
nazardovhanich nazardovhanich  17.12.2021 12:40

х = 3

Пошаговое объяснение:

12 + (4x – 12) – 2x = (5 – 3x) + 10

12 + 4х - 12 - 2х = 5 - 3х + 10

2х = 15 - 3х

2х + 3х = 15

5х = 15

х = 15/5

х = 3

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика